2001
DOI: 10.1099/0022-1317-50-6-547
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of a 17-kDa staphylococcal heparin-binding protein with broad specificity

Abstract: A previous study reported the ability of staphylococci to bind heparin and heparindependent host growth factors. The present study isolated and identi®ed heparin-and basic ®broblast growth factor (bFGF)-binding surface components of S. epidermidis strain RP12 and S. haemolyticus strain SM 131. The staphylococcal heparin-binding component(s) were puri®ed by af®nity chromatography on heparin-Sepharose and a major heparin-binding protein, here designated HBP, was identi®ed by immunoblot in these two coagulase-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This pathogen might contain surface proteins that bind HA and facilitate its incorporation into the biofilm structure. Heparin and eDNA binding proteins have been identified in a number of bacteria, including S. aureus (45)(46)(47)(48)(49)(50), lending support to this idea. Due to the high degree of HA association with the individual cell surfaces in S. aureus biofilm (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…This pathogen might contain surface proteins that bind HA and facilitate its incorporation into the biofilm structure. Heparin and eDNA binding proteins have been identified in a number of bacteria, including S. aureus (45)(46)(47)(48)(49)(50), lending support to this idea. Due to the high degree of HA association with the individual cell surfaces in S. aureus biofilm (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…These data suggests that heparin stimulates the formation of adhesion molecules that make S. aureus better able to adhere to one another in either a heparindependent (where heparin acts as a cross-bridge) or heparinindependent manner. Consistent with this hypothesis, several groups have evidence suggesting that S. aureus codes for a heparin binding protein (14,16,37). Pascu and colleagues found that 30 of 38 coagulase-negative staphylococci were able to aggregate to heparin-coated beads and this binding was inhibited by several sulfated molecules (48).…”
Section: Discussionmentioning
confidence: 56%
“…Although some parasites can bind to multiple GAGs (Coppi et al, 2007;Fallgren et al, 2001), heparan sulfate proteoglycan (HSPG) has been implicated in the recognition and/or invasion process of a wide range of pathogens, including viruses, bacteria and protozoan parasites (Bambino-Medeiros et al, 2011;Dalrymple & Mackow 2011;Yan et al, 2006;). Despite the role of heparin-binding proteins in many physiological and pathological processes, the basis of the heparin-protein interaction at the molecular level is still unclear.…”
Section: Role Of Heparin-binding Proteins In Pathogen-host Cellmentioning
confidence: 99%
“…HBPs from S. aureus have been demonstrated to be sensitive to heat and proteases, such as pronase E, proteinase K, pepsin and chymotrypsin (Liang et al, 1992). Interestingly, a 17-kDa heparin-binding protein with pI 4.6 has also been isolated from S. epidermis and S. haemolyticus, but the amino acid sequence similarity is low between these two organisms (MXTAHSYTXKYNGYTAN and MATQTKGYYYSYNGYV, respectively) and other bacterial HBPs (Fallgren et al, 2001). …”
Section: Role Of Heparin-binding Proteins In Pathogen-host Cellmentioning
confidence: 99%